Successful HCV Therapy Reduces Liver Disease Severity and Inflammation Biomarkers in HIV/HCV-Coinfected Patients With Advanced Cirrhosis: A Cohort Study - Medrano, Luz Maria; Berenguer, Juan; Salgüero, Sergio; González-García, Juan; Díez, Cristina; Hontañón, Víctor; Garcia-Broncano, Pilar; Ibañez-Samaniego, Luis; Bellón, José M.; Jiménez-Sousa, María Angeles; Resino, Salvador (Frontiers in Medicine, 2021)
Background: Eradication of hepatitis C virus (HCV) promotes an improvement in liver disease and the deactivation of the immune system. Here, we aimed to evaluate the changes in liver disease scores and plasma biomarkers following HCV clearance with direct-acting antivirals (DAAs) in HIV-infected patients with advanced HCV-related cirrhosis. Methods: We performed an observational study of 50 patients with advanced cirrhosis who received DAAs therapy. Variables were assessed at baseline and 48 weeks after HCV treatment completion. Epidemiological and clinical data were collected through an online form. Liver stiffness measurement (LSM), hepatic venous pressure gradient (HVPG), and Child-Pugh-Turcotte (CTP) were evaluated by physicians. Plasma biomarkers were measured by multiplex immunoassay. Results: We found significant decreases in severity scores of liver disease [LSM (q-value < 0.001), HVPG (q-value = 0.011), and CTP (q-value = 0.045)] and plasma biomarkers [LBP (q-value < 0.001), IP-10 (q-value < 0.001), IL-8 (q-value < 0.001), IL-18 (q-value < 0.001), IL-1RA (q-value = 0.013), OPG (q-value < 0.001), sVCAM-1 (q-value < 0.001), sICAM-1 (q-value < 0.001), PAI-1 (q-value = 0.001), and VEGF-A (q-value = 0.006)]. We also found a significant direct association between the change in LSM values and the change in values of LBP (q-value < 0.001), IP-10 (q-value < 0.001), MCP-1 (q-value = 0.008), IL-8 (q-value < 0.001), IL-18 (q-value < 0.001), OPG (q-value = 0.004), sVCAM-1 (q-value < 0.001), sICAM-1 (q-value < 0.001), and PAI-1 (q-value = 0.002). For CTP values, we found significant positive associations with IP-10 (q-value = 0.010), IL-6 (q-value = 0.010), IL-1RA (q-value = 0.033), and sICAM-1 (q-value = 0.010). Conclusion: The HCV eradication with all-oral DAAs in HIV/HCV-coinfected patients with advanced cirrhosis promoted an improvement in the severity of advanced cirrhosis and plasma biomarkers (inflammation, coagulopathy, and angiogenesis). The decrease in plasma biomarkers was mainly related to the reduction in LSM values.